Sustainable Financing for Developement : Four Essays on Resource Mobilization in Africa - (:unkn) unknown (My University, 2019)
Domestic resource mobilization and external financial flows are crucial for financing Sustainable Development Goals in Africa and the development objectives outlined in the African Union Agenda 2063. Financing for development in Africa is at the heart of this dissertation. We divided the dissertation into two parts. The first part comprising chapters 1 and 2 focuses on domestic tax revenue mobilization while the second part composed of chapters 3 and 4 deals with the issue of attracting one of the most important external financial flows, namely foreign direct investments.Chapter 1 analyses the relationship between natural resources wealth and non-resource tax revenue in Africa. Three important results emerge from this chapter. The direct impact of natural resource rents on non-resource tax revenue is negative. However, natural resource rents positively affect non-resource tax revenue in countries with good institutional quality. Moreover, we find evidence that natural resource rents enhance non-resource tax mobilization in countries with greater economic diversification. These findings provide additional motivations to African governments to further increase the emphasis on economic diversification and to strengthen the quality of institutions so that natural resources revenues contribute to boost non-resource tax revenue mobilization in the continent. Chapter 2 examines the impacts of social indicators, income inequality and poverty on non-resource tax revenue performance in Sub-Saharan Africa since the social environment in which taxes are collected could affect tax collection performances. We find that both income inequality and poverty reduce non-resource tax revenue in Sub-Saharan Africa. In terms of policy implication, these findings help inform policymakers that reducing income inequality and poverty could be viewed not only as a crucial dimension of development or a vector of social justice, but also an important engine of non-resource tax rev
Keywords: African Research